TPACK-based HOTS in Teaching Writing for Promoting EFL Learning Quality on Higher Education: Applying “Program Merdeka Belajar – Kampus Merdeka and Kurikulum Paradikma Baru” - Bagus Waluyo; Umi Nahdiyah; Cholida Indrian Fahriana (Journal of Development Research, 2023)
The purpose of the study is to describe the technology on TPACK-based HOTS applied by lecturers of a suburban university in teaching writing, and its challenge faced in-class interaction. Four English lecturers from Universitas Nahdlatul Ulama Blitar in Indonesia are the participants selected using the purposive sampling design. The process of data collection uses depth interviewing through the online system. Data are analyzed using a "holistic" viewpoint in case study. The results revealed that simple technology dominates the general interactions when teaching writing. Some lecturers may only have a basic understanding of utilizing technology to teach writing. Even they still favour using manual teaching. Because the internet network is poor, few students have technology equipment like laptops, and the interaction is tedious because students are unfamiliar with the technology. It is better that the government, schools, the community, and the primary critical holders for learning must work together in determining policies in the face of changes to use technology in all aspects of school interaction.